2017
DOI: 10.21834/ajbes.v2i6.43
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Characteristics of Children’s Neighborhood Activities

Abstract: Environmental characteristics affecting children’s physical abilities and health are worth understanding. The purpose of this study is to identify neighborhood environmental characteristics that influence children’s activities and assess the friendliness of Taiwanese communities toward children’s activities. Conditions are observed on the basis of five environmental characteristics: safety, amenity, accessibility, sociability, and attractiveness. The three communities studied have different combinations of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this technological era, children are more likely to spend more time indoors, playing video games, watching television and engaging in the social media on the Internet. Zhang and Li (2010) found that the numbers of children performing outdoor recreation activities all over the world are decreasing in the past few years. In Malaysia, the Economic Planning Unit (2011) listed health, environment and social participation among the components to measure quality of life.…”
Section: Urban Parks and The Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…In this technological era, children are more likely to spend more time indoors, playing video games, watching television and engaging in the social media on the Internet. Zhang and Li (2010) found that the numbers of children performing outdoor recreation activities all over the world are decreasing in the past few years. In Malaysia, the Economic Planning Unit (2011) listed health, environment and social participation among the components to measure quality of life.…”
Section: Urban Parks and The Quality Of Lifementioning
confidence: 99%
“…Well maintained parks provide venues for recreational and physical activities among the urban community to improve health and maintain fitness. Zhang and Li (2010) stated that accessible parks, playground and recreational facilities help in increasing physical activities and less sedentary activities. Besides the physical health benefits, nature and recreation are also important for social and psychological development (Chiesura 2004;Khotdee et al 2011).…”
Section: Health Benefitsmentioning
confidence: 99%